2007
DOI: 10.1186/1742-6405-4-10
|View full text |Cite
|
Sign up to set email alerts
|

Media and education play a tremendous role in mounting AIDS awareness among married couples in Bangladesh

Abstract: BackgroundTo quarantine the spreading possibility of HIV virus to general population boosting public awareness is must. But the proper awareness level is substantially low in Bangladesh. This paper aims to identify the factors associated with the awareness regarding HIV/AIDS through a bivariate and multivariate analysis using the data extracted from Bangladesh Demography and Health Survey (BDHS) 1999–2000.ResultsThe findings of both techniques show that education, occupation, socioeconomic status, status of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 12 publications
12
48
0
Order By: Relevance
“…The present study provides evidence of their low income (≤5000 TK monthly) and low expenditures (≤5000 TK monthly) representing a low standard of living. Consistent with other studies [12][13][14] the findings indicate that education predicts the level of HIV/AIDS awareness and reiterates the importance of education for Bangladesh. The findings of this study also suggest that the respondents are not sufficiently conscious about contraceptive use, but contraceptive usage was found to be an important factor for HIV/AIDS awareness [15].…”
Section: Discussionsupporting
confidence: 81%
“…The present study provides evidence of their low income (≤5000 TK monthly) and low expenditures (≤5000 TK monthly) representing a low standard of living. Consistent with other studies [12][13][14] the findings indicate that education predicts the level of HIV/AIDS awareness and reiterates the importance of education for Bangladesh. The findings of this study also suggest that the respondents are not sufficiently conscious about contraceptive use, but contraceptive usage was found to be an important factor for HIV/AIDS awareness [15].…”
Section: Discussionsupporting
confidence: 81%
“…However, it also shows in the data that education status may affect one's occupation, wealth status and attitudes to PLHIVs (Rahman & Rahman, 2007). This study found education to be a significant predictor of having comprehensive HIV and AIDS knowledge, a finding consistent with studies carried out in other countries in the sub-region (Mishra et al, 2009).…”
Section: Trends In Hiv/aids Knowledge In Ghanasupporting
confidence: 81%
“…It is a relatively inexpensive way of exposing the population to information regarding their health [2] and has the potential to reach a large proportion of the population, particularly groups that may be difficult to access through more traditional approaches [5,9,[9][10][11]. For instance, mass media campaigns based on communication for behavioral impact and social change have been shown to be an effective intervention for smoking cessation in adults [12][13][14][15][16]. In the case of a vaccine preventable disease, people may opt to vaccinate more, and, promptly, when the perceived risk from the disease is high, and little (and later) otherwise [17].…”
Section: Introductionmentioning
confidence: 99%